Quality Assurance in Ghana: Accomplishments and Challenges - Swanzy, Patrick; Langa, Patricio V.; Ansah, Francis (International Higher Education, 2018)
This article examines Ghana’s efforts to revitalize its higher education system using quality assurance (QA). Specifically, we discuss the accomplishments and challenges of the QA system. Ghana has one of the oldest QA systems in Africa, so lessons learned there are worth sharing with scholars and practitioners.